THERAPEUTIC POTENTIAL OF USING PROBIOTICS IN THE TREATMENT AND PREVENTION OF BREAST CANCER - Soares, Tiago; Silva, Bruna Barbosa Maia da; Araújo, Danielle Silva; Feijó de Figueiredo, Maria Clara; Leal Bezerra, Francisco das Chagas; Silva, Eliakim Aureliano da; Pereira Sousa, Ana Cibele; Arcanjo Medeiros, Stella Regina; Barbosa, Celma de Oliveira; Pereira-Freire, Joilane Alves (Journal of Health & Biological Sciences, 2021)
Introduction: Probiotics are living microorganisms that when administered in appropriate amounts, provide several benefits such as prevention of infections, relief of allergic symptoms and lactose intolerance, control of serum cholesterol, blood pressure and gestational diabetes, reduction of gastrointestinal disorders, production of beneficial compounds such as vitamins, short chain fatty acids, and such microorganisms show evidence of actions against certain types of cancers. This study aimed to evaluate the evidence available in the literature on probiotics on breast cancer. Methods: It is an integrative review of the literature, through the PICO strategy, with the guiding question “Does probiotics consumption act on oxidative stress and reduces the risk of breast cancer”? The selection of articles was made on MEDLINE, SciELO and PubMed, including those published between 2016 and 2021, using the keywords: “breast cancer” AND “probiotics” AND “microbiota” their combinations in Portuguese and English, with with previously established inclusion criteria. Results and Discussion: The sample consisted of ten articles, and the answers found were: scientific research in vivo and in vitro, with some variations of probiotics strains, where all demonstrate actions and/or effects on cancer cells or acted on metabolic pathways mitigating the development of tumors. Conclusions: The manifested potential for a possible insertion in the treatment and prevention of breast cancer, being considered an innovation for the scientific community that still fights against various types of problems related to human health, especially some types of cancers, of negative prognoses and with difficult therapeutic interventions.